Pelaksanaan Pelayanan Kesehatan Penyandang Disabilitas: Perspektif Fiqih Siyasah - Mustika, Rindy; Yoki Pradikta, Hervin (As-Siyasi: Journal of Constitutional Law, 2021)
Article 12 Sub C of Law Number 8 of 2016 concerning Health Services for Persons with Disabilities is present by giving responsibility to the government for the right to health services for persons with disabilities. As explained in Article 12 of Law Number 8 of 2016 namely: "That persons with disabilities have the right to obtain equality and opportunity for safe, quality, and affordable health services". Persons with disabilities are also citizens of the Republic of Indonesia who in the 1945 Constitution are guaranteed to have the same position, rights, obligations and roles as other citizens. Inpatient Puskesmas Katibung South Lampung is a health center that has the widest working area compared to other health centers in Katibung, South Lampung. So the Katibung Inpatient Health Center, South Lampung, plays an important role in providing health services for all people in the working area of the health center, without exception for people with disabilities. The formulation of the research problem is how to the right to health services for persons with disabilities from the fiqh siyasah perspective at the Katibung Inpatient Health Center. This study aims to determine how the implementation of the fulfillment of the right to health services for persons with disabilities in the fiqh siyasah perspective at the Katibung Inpatient Health Center. As for this writing, using field research methods means that this research is carried out by going directly to the field that will be the object of research. Sources of data used in this study are secondary data such as books, journals, government publications and primary data such as observations and interviews, so as to obtain primary data it is clear that a population and sample are needed in this study. The total population in this study was 159 people and took a sample of 10 people using purposive sampling technique. In this study, it was revealed that health services for persons with disabilities were still not fully fulfilled due to the absence of information and data collection, stigmatization and socio-cultural factors.